1996
DOI: 10.1002/art.1780390908
|View full text |Cite
|
Sign up to set email alerts
|

Renal biopsy findings and followup of renal function in rheumatoid arthritis patients treated with cyclosporin A. An update from the international kidney biopsy registry

Abstract: The data indicate that in RA patients being treated according to current dosing recommendations, the risk of developing CSA-induced nephropathy is low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 15 publications
0
16
0
1
Order By: Relevance
“…[18][19][20][21][22][23][24][25] The toxicity, which is particularly increased in the presence of serum creatinine and hypertension, is considered manageable if dosage guidelines are strictly maintained. 20 [26][27][28] In a number of studies it has been suggested that radiological progression is retarded by CsA in comparison with placebo or other DMARDs. [29][30][31] Because both drugs have different mechanisms of action, and their toxicity patterns do not overlap, the combination of MTX with CsA may offer complementary efficacy.…”
mentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25] The toxicity, which is particularly increased in the presence of serum creatinine and hypertension, is considered manageable if dosage guidelines are strictly maintained. 20 [26][27][28] In a number of studies it has been suggested that radiological progression is retarded by CsA in comparison with placebo or other DMARDs. [29][30][31] Because both drugs have different mechanisms of action, and their toxicity patterns do not overlap, the combination of MTX with CsA may offer complementary efficacy.…”
mentioning
confidence: 99%
“…The use of cyclosporine, however, has been limited by its toxicity, especially hypertension and dose-related loss of renal function (114,115). The ϳ20% loss of renal function with cyclosporine appears to be largely, but not entirely, reversible with discontinuation of the drug (115,116). Dose calculation to avoid renal toxicity is more critical with cyclosporine than with any other DMARD.…”
Section: Pharmacologic Treatment Of Ramentioning
confidence: 99%
“…It is thought that the impaired renal function is reversible for treatment periods of under two years but that beyond this time, irreversible changes in renal function may occur. However biopsy studies of long term use of low-dose CsA in rheumatoid arthritis have shown that this risk is very low [54]. Opportunistic infections do not appear to be a significant problem with low dose CsA unless very high doses of oral corticosteroids or concomitant treatment with another immunosuppressant are used.…”
Section: Csamentioning
confidence: 99%